Oligonucleotide aptamers: promising and powerful diagnostic and therapeutic tools for infectious diseases. Issue 2 (August 2018) - Pan, Qin; Luo, Fengling; Liu, Min; Zhang, Xiao-Lian
Summary: The entire human population is at risk of infectious diseases worldwide. Thus far, the diagnosis and treatment of human infectious diseases at the molecular and nanoscale levels have been extremely challenging tasks because of the lack of effective probes to identify and recognize biomarkers of pathogens. Oligonucleotide aptamers are a class of small nucleic acid ligands that are composed of single-stranded DNA (ssDNA) or RNA and act as affinity probes or molecular recognition elements for a variety of targets. These aptamers have an exciting potential for diagnose and/or treatment of specific diseases. In this review, we highlight areas where aptamers have been developed as diagnostic and therapeutic agents for both bacterial and viral infectious diseases as well as aptamer-based detection.